2018
DOI: 10.1371/journal.pone.0209547
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of manual annotations of clinical text with SNOMED CT

Abstract: SNOMED CT provides about 300,000 codes with fine-grained concept definitions to support interoperability of health data. Coding clinical texts with medical terminologies it is not a trivial task and is prone to disagreements between coders. We conducted a qualitative analysis to identify sources of disagreements on an annotation experiment which used a subset of SNOMED CT with some restrictions. A corpus of 20 English clinical text fragments from diverse origins and languages was annotated independently by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…Research aim to identify these codes from medical free texts or to map their domain ontological systems to standards for better interoperability. Miñarro-Giménez et al 35 represented the example of manual annotation of medical free texts with SNOMED CT codes by experts. The limitations of this approach are connected mainly with human factor and specializations of recruited experts.…”
Section: Terminology Codes Assignmentmentioning
confidence: 99%
“…Research aim to identify these codes from medical free texts or to map their domain ontological systems to standards for better interoperability. Miñarro-Giménez et al 35 represented the example of manual annotation of medical free texts with SNOMED CT codes by experts. The limitations of this approach are connected mainly with human factor and specializations of recruited experts.…”
Section: Terminology Codes Assignmentmentioning
confidence: 99%
“…Quantitative morphologic measurements of the arterial vessel wall and plaques based on MRVWI have been proven to have good reproducibility ( Mandell et al, 2017 ; Saba et al, 2018 ; Zhang et al, 2018 ) and suggested to be imaging markers to monitor the progression and regression of ischemic stroke during medical management or drug development ( Adams et al, 2004 ; Minarro-Gimenez et al, 2018 ). However, quantitative measurements are currently of limited use in clinical practice because manual segmentation of the vessel wall and plaque is labor intensive and requires continuous training of personnel ( Qiao et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other classification systems exist for annotation of veterinary clinical notes covering a much wider range of diagnoses and syndromes [ 6 , 7 ] but may also be incompletely used at point of care requiring additional search methods (such as key word matching) and manual reading to detect syndrome occurrence [ 8 ], restricting their utility for real-time surveillance. Additionally, regardless of who applies them, clinical coding systems may fall victim to inaccurate, inconsistent and incomplete coding by users [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%